Graphene oxide supported mononuclear aquaruthenium complex ultrathin films with enhanced photoelectric conversion and electrocatalytic water oxidation. (1st August 2015) - Xue, Long-Xin; Meng, Ting-Ting; Zhao, Yue; Gao, Li-Hua; Wang, Ke-Zhi
Graphical abstract: A electrostatic film composed of GO nanosheets and a Ru(II) complex on ITO exhibited quasi-reversible redox behaviors with rapid heterogeneous electron transfer dynamics, and remarkably improved electrocatalytic water oxidation and photoelectric conversion properties as compared with the electrodes with polyanionic being the support for the Ru(II) complex. Abstract: A new Ru(II) complex of [Ru(tpy)(Htip)(H2 O)] 2+ {tpy = 2, 2′, 2″-terpyridine, Htip = 2-(thiophen-2-yl)-1 H -imidazo[4, 5- f ][1, 10]-phenanthroline} is synthesized and characterized. A layer-by-layer deposition of equal amounts of graphene oxide (GO) and the Ru(II) complex on hydrophilic substrates through electrostatic attraction of these two components was evidenced by X-ray photoelectron and UV–visible absorption spectroscopy. Permeability of the film to the redox probe [Fe(CN)6 ] 3−/4− was studied by cyclic voltammetry and electrochemical impedance spectroscopy. The films showed stable electrochemical and photoelectrochemical properties with photocurrent densities of 6.6 μA/cm 2 being found for a monolayer film and 9.7 μA/cm 2 for a 4-layer film, which is much improved as compared to GO monolayer alone and the film by using a polyanion instead of the GO. The enhanced electrocatalytic water oxidation properties of this hybrid film have also been demonstrated. Preliminary results of electrocatalytic water oxidation by this hybrid film is also reported.